(untitled) (Development Engineering Conferences Center Articles Database, 2026)
The presence of scattered sources and micro-grids in power systems, despite the economic and environmental advantages, have added new problems to power systems.Among these problems, voltage and frequency fluctuations can be mentioned when possible events occur, such as extreme load changes or errors in the power system. In the island mode, due to the lack of backup power, the intensity and range of these fluctuations and the possibility of instability in the microgrid are much higher. In this paper, we study how to control the voltage, frequency and power supply required by load in a microgrid. Microgrid is a small low voltage power supply grid. It has two work modes:grid-connected mode and islanded mode.The most important challenge in using the microcontroller grid is to provide better control of distributed generations (DG) by connecting it to the microgridwith an inverter interface. Therefore, the main purpose is to control the inverters. In this paper, a drop-down control technique is proposed to control voltage and frequency of the microgrid and the power allocation between microgrids. The advantage of this method is using a single controller in both work modes. Also, there is no need for communication grids between micro components.